ANALISIS MASALAH DALAM KONTEKS PENDIDIKAN DENGAN PERSPEKTIF GLOBAL DI SEKOLAH DASAR - Irsanti, Kurnia; Rama Lestari , Sruni; Noviyanti, Silvina (Yayasan Amanah Nur Aman, 2025)
Education with a global perspective at the elementary school level is a strategic approach in shaping the character of students who care, think critically, and have broad insights from an early age. This article examines a number of global issues such as the environment, human rights, social inequality, cultural migration, and the development of information technology, and explores how these issues can be integrated into contextual, fun, and relevant learning for elementary school students. The role of teachers as learning facilitators is crucial in realizing global education through thematic, project-based approaches and strengthening multicultural literacy. This approach is in line with the values of the Pancasila Student Profile and contributes to forming a generation that is ready to face global challenges, without losing the roots of national identity and culture.